Association of free fatty acids with the insulin-resistant state but not with central obesity in individuals from Venezuela. - Campos, Gilberto; Fernández, Virginia; Fernández, Erika; Molero, Emperatriz; Morales, Luz Marina; Raleigh, Xiomara; Connell, Lissette; Ryder, Elena (Investigación Clínica, 2013)
Â  Individuals with insulin resistance (IR) usually have upper body obesity phenotype, often accompanied by an increase in plasma free fatty acids (FFA). Since the Venezuelan population has a high frequency of IR and central obesity, the purpose of this work was to determine FFA levels in 47 Venezuelan individuals, men and women, 24-58 years old, and analyze their relationship with central obesity and parameters of carbohydrate and lipid metabolism. Basal concentrations of TG, total cholesterol, LDL-C, and HDL-C were measured, and FFA, glucose and insulin, at basal state and at different times after a glucose load. Eighteen individuals presented insulin resistance (HOMA-IR >2.7) and 29 were non-insulin resistant (non-IR). Insulin resistant individuals (IR) had higher waist circumference, BMI and basal concentrations of FFA than the non-IR. No differences were observed in skin folds and other basal lipids studied. The increased FFA seemed to be related to the IR associated to BMI and not to central obesity, since the difference between IR and non-IR disappeared when they were matched for waist circumference. After a glucose load, FFA decreased in both groups, but remained significantly elevated in IR subjects. This effect disappeared after matching for BMI or waist circumference, inferring that it was independent of anthropometrics. FFA were positively associated with HOMA-IR, glucose and TG levels; however, there was no association with BMI or waist circumference. These findings, and the lack of elements to support the presence of hepatic IR, common to in- creased visceral lipolysis, might suggest that the IR present in the obese individuals studied, might be due to an increase in subcutaneous fat.